Analisis Tindak Tutur Ilokusi dalam Video Podcast PDP Episode 46 di Akun Youtube Kaesang Pangarep by GK Hebat - Nurikmah Nurikmah; Arief Fiddienika (FKIP, Universitas Palangka Raya, 2026)
The background of this research is the analysis of speech acts in conversations on the podcast show featured on Kaesang Pangarep's YouTube channel by GK Hebat. The purpose of this study is to analyze the forms of illocutionary speech acts in the dialogue between the guest star (Rina Nose) and the hosts (Kiki Saputri, Kaesang Pangarep, and Ate) in the PDP Episode 46 podcast video on Kaesang Pangarep's YouTube channel by GK Hebat. This research utilizes a descriptive approach combined with qualitative methods. The objects of this research are the utterances delivered by the hosts (Kaesang Pangarep, Kiki Saputri, and Ate) and the guest star (Rina Nose). The findings of this study indicate five types of illocutionary speech acts: declarative, expressive, directive, commissive, and assertive. The study recorded a total of 47 instances, comprising 24 assertive utterances, 6 commissive utterances, 6 directive utterances, 4 declarative utterances, and 8 expressive utterances. Assertive speech acts include verbs such as informing, stating, boasting, mentioning, and expressing opinions. Directive speech acts encompass suggesting, advising, and urging. Declarative speech acts involve deciding, prohibiting, and allowing. Commissive speech acts include offering, threatening, and promising. Finally, expressive speech acts cover praising, complaining, and expressing gratitude.